PENGEMBANGAN MEDIA LUDO MATH PADA MATERI PECAHAN SEDERHANA BAGI PESERTA DIDIK KELAS III SEKOLAH DASAR - Alfiatun Nur Azizah; Meita Fitrianawati (PGSD Universitas Muria Kudus, 2020)
This research aims to determine the steps of media development and to know the quality and feasibility of Ludo Math media.The Ludo Math media was developed with a Borg and Gall model consisting of; 1) research and information collecting, 2) planning, 3) develop preliminary form of product, 4) preliminary field testing, 5) main product revision, 6) main field testing, 7) operational product revision, and 8) operational field testing. The study was conducted at SD NegeriGetas 02 with the subject students training class III. Data collection techniques in the form of observation, interviews, assessment sheets of experts and teachers, and student response sheets.Analysis of the data of this study includes qualitative data analysis and quantitative data analysis. The results of this study indicate that the assessment according to media experts obtained a value of 85 with the category